Synthesis and characterization of titanium dioxide doped nickel oxide dielectric materials (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Nickel oxide (NiO) belongs to the transition metal oxide family, having good dielectric constantwith the range of 103 – 105, but it has high dielectric loss. In this research, the effect of titaniumdioxide (TiO2) addition into NiO was investigated. Generally, TiO2 was used in the application ofelectrical ceramic, catalysts, electric conductors and chemical intermediates. Ni1-xTixO1+x wasprepared via solid-state reaction method with 6 different TiO2 compositions. The preparation startedwith the powder mixing process for 24 hours and followed by calcination process at 950 °C for 4hours. Then, the calcined powders were compacted into 6 mm pellet shape under pressure of 250MPa pressure. Three pellets were made for each TiO2 composition. Those pellets were sintered at1250 °C for 5 hours. XRD results showed that pure NiO at 0.01 and 0.02 mole % of TiO2compositions produced single NiO crystalline phase, while 0.03, 0.05 and 0.10 mol % of TiO2showed the TiO2, instead of NiO phases. SEM analysis showed that increasing TiO2 concentrationmake the grain size increase, with 0.02 mole % of TiO2 gave the largest grain size, shows that 0.02mole % is the optimum TiO2 concentration for grain size enlargement. Furthermore, the bulkdensity of Ni1xTixO1+xpellet was reduces at higher TiO2 concentration. In dielectric test, the additionof 0.03 mole % of TiO2 gave the highest dielectric constant with value of 4.51 x 1014 and 0.05 mole% of TiO2 gives the result of lowest dielectric loss (0.53).
Keywords: dopant; solid-state reaction; ceramic; dielectric constant; dielectric loss